Fall field reports, 1999, Jim Dinsmore - Dinsmore, James J.et al (1999)
An annotated list of birds sighted by Jim Dinsmore. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1999. Epson - sheet feed